EFFECTS OF AQUATIC PHYSIOTHERAPY ON LUNG FUNCTION AND LIFE QUALITY IN PATIENTS WITH BREAST CANCER (Fiep Bulletin - online, 2012)
The cancer (CA) of the breast can result in physical changes that cause loss of life quality (QL). The aquatic physiotherapy (AP) improves the cardiorespiratory capacity, which can reduce problems stemming from the disease. Thus, this study aimed to evaluate lung volumes, respiratory muscle strength (RMS) and QL before and after AP program in women with breast CA. It is a pre-experimental study, which included 11 patients with breast CA after chemotherapy. The AP program included 34 sessions (03 a week), comprising 15 minutes of aerobic exercise (warming up), 15 minutes of stretching, 10 minutes of resistance exercises and 10 minutes of relaxation. Physiological variables (blood pressure, heart rate [HR], oxygen saturation and respiratory rate [RR]), lung volumes, maximal inspiratory pressure (MIP), maximal expiratory pressure (MEP) and QL were measured before and after the AP program. The average age and BMI were 52.82 ± 7.22 years old and 24.99 ± 3.36 kg/m2, respectively. After the AP program, a reduction in HR (p = 0.018) and RR (p = 0.003) as well as increased MIP (p = 0.022) and MEP (p = 0.026). The lung volumes did not change, however, the QL significantly improved (p = 0.029). It is concluded that AP reduced the breathing and cardiac function as well as improved quality of life and RMS, demonstrating the positive impact of the aquatic physiotherapy program in patients with breast cancer.
Keywords: breast cancer; physiotherapy; muscle strength; quality of life